An innovative technique for improved production from depillaring panel in an underground coal mine - Alam S.; Rai P. (My University, 2025)
System analysis approach has been used in the present field based research paper for a deep and gassy coal mine of Jharia coalfields. The working panel was considered as a system that was splitted into various sub-systems. The subsystems were statistically analyzed to compute the production capacity of various sub-systems. Reserve capacity of various sub-systems was also estimated. Additionally, a modified depillaring method has been mootedfor enhanced production and productivity level from side discharge loader (SDL) in depillaring panel for given set of manpower and face preparation equipment. Tangible benefits, non-Tangible benefits, requirements for its success have also been discussed.